Accelerated activation of SOCE current in myotubes from two mouse models of anesthetic- and heat-induced sudden death. - Viktor Yarotskyy; Feliciano Protasi; Robert T Dirksen (PLoS ONE)
Store-operated calcium entry (SOCE) channels play an important role in Ca(2+) signaling. Recently, excessive SOCE was proposed to play a central role in the pathogenesis of malignant hyperthermia (MH), a pharmacogenic disorder of skeletal muscle. We tested this hypothesis by characterizing SOCE current (ISkCRAC) magnitude, voltage dependence, and rate of activation in myotubes derived from two mouse models of anesthetic- and heat-induced sudden death: 1) type 1 ryanodine receptor (RyR1) knock-in mice (Y524S/+) and 2) calsequestrin 1 and 2 double knock-out (dCasq-null) mice. ISkCRAC voltage dependence and magnitude at -80 mV were not significantly different in myotubes derived from wild type (WT), Y524S/+ and dCasq-null mice. However, the rate of ISkCRAC activation upon repetitive depolarization was significantly faster at room temperature in myotubes from Y524S/+ and dCasq-null mice. In addition, the maximum rate of ISkCRAC activation in dCasq-null myotubes was also faster than WT at more physiological temperatures (35-37°C). Azumolene (50 µM), a more water-soluble analog of dantrolene that is used to reverse MH crises, failed to alter ISkCRAC density or rate of activation. Together, these results indicate that while an increased rate of ISkCRAC activation is a common characteristic of myotubes derived from Y524S/+ and dCasq-null mice and that the protective effects of azumolene are not due to a direct inhibition of SOCE channels.